DETERMINASI PATOKAN WAKTU PABRIKASI DENGAN STOPWATCH TIME STUDY (STUDI KASUS CEMILAN SBR) - Asri Amalia Muti; Tri Novita Sari; Novan Hadi Ahmad (Universitas Putera Batam, 2022)
SBR Snacks, engaged in food, produces various kinds of snacks such as bread, banana chips and opak gambier. The problem in this industry is that when ordering the same product, if the manufacturing process is different for each order, there will be delays in the manufacturing process. In this study, a time study was conducted by observing three products commonly produced by the domestic industry from these snacks. Based on the time survey conducted, it was found that there is no set time standard for the manufacturing process of each product. Adjustment and tolerance procedures are used when setting the standard time. From the results of the study, the standard time for each product was 1670.34 seconds for bread products, 2205.84 seconds for banana chips, 2268.84 seconds for opaque gambier.